On Hadamard-type inequalities for m-convex functions via Riemann-Liouville fractional integrals - FARID, Ghulam; REHMAN, Atiq Ur; TARIQ, Bushra (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this paper we prove the Hadamard-type inequalities for m-convex functions via Riemann-Liouville fractional integrals and the Hadamard-type in- equalities for convex functions via Riemann-Liouville fractional integral are deduced. Also we find connections with some well known results related to the Hadamard inequality. Mathematics Subject Classification (2010): 26A51, 26A33, 26D10.